“Efecto de baculovirus en los diferentes estadios larvales del cogollero (spodoptera grugiperda) en el cultivo del maíz amarillo duro (zea mays) M-28 en Juan Guerra” - García Tuesta, Wagner Luis (2003)
The current research was carried out between the months of January to May of 2 001, in order to find the limit age for the application of the baculovirus to larvae and the effects that it has on the larvae stages of the "Fall army worm" (Spodoptera frugipercla J. E Smith) in the cropping of com. The field work phase was developed in the installations of the "El Porvenir'' Experimental Center in the district of Juan Guerra, in the Province, Department and Region of San Martín, located between latitude south 6° 35', longitude west 76° 19' and an altitude of 232 m. a. s. l. The experimental design used was the full random blocks (FRB) with 04 repetitions and 05 treatments. There were recollected larvae of "fall army worm" in the com fields of the "El Porvenir'' Experimental Center, and then the larvae were brought to the U.N.S.M laboratory of Entomology for the mass breeding, so in that way uniform the ages among the larvae subject of study. The infestations were done since 30 days after the sowing. the baculovirus applications were done 24 hours after each infestation . The dose applied was 100 g/ha. The results of larvae mortality achieved after evaluations were carried out were: T1 = 96,50%; T2 = 81,50%; T3 = 69,00%; T4 = 62,50% y Ts = 49,00%; where it can be mentioned that the limit age for the application of the baculovirus is comprised until the third larval stage (20 mm long or 11 days of age), apart from working with a great efticiency at totality of the larval stages.